Trajetórias de formação em ambientes virtuais : entendimentos e percepções da mediação, interação e interatividade - Silva, Danilo Garcia da (2015)
ABSTRACT In Education area, the communicational and pedagogical potential added by Digital Technologies of Communication and Information, and Virtual Learning Environments is recognized starting from the exploration of their potentials. The most varied technological resources have been established as the possible universe, when it is related to the promotion of Education in its diverse levels. In this universe, this research is sustained by the idea that mediation, interaction, and interactivity– here named as socio-historical elements in online training, are components of the formation paths and they determine the relations and roles of the learning subjects in online formation. In order to do so, we adopt the next issue: what are the understandings and perceptions made by the learning subjects in online formation paths in the courses of Universidade Aberta do Brasil of Universidade Federal de Mato Grosso about the elements mentioned before? Thus, the objective of this research is firmed in the comprehension of the understandings and perceptions of the learning subjects about mediation, interaction, and interactivity from the relations that they establish during the online training trajectory, once they determine the function of these subjects in the teaching and learning process in online courses. Given the characteristic of this object of study, the option was through the qualitative research (DENZIN; LINCOLN, 2006) in Education; with multirreferencial approach (ARDOINO, 1998). This study has as locus the undergraduate courses that take part in the program system of Universidade Aberta do Brasil of Universidade Federal de Mato Grosso, that is to say: Administração Pública 2009, Ciências Naturais e Matemática 2009, Pedagogia 2009 and Pedagogia Acordo Brasil/Japão, all in online formation. The subjects of the research are the coordinators, professors, tutors, and students. The tools for collecting the results are documental analysis, observations, reports, questionnaires, and interviews. We achieved 204 questionnaires, 19 interviews with students, 5 interviews with coordinators, 3 interviews with tutors, and 17 interviews with professors. The findings were organized in meaning cores, basing on the socio-historical elements in study. Thus, it is admitted that mediation, interaction, and interactivity are expensive elements for the online training, therefore, they are not performed, just in virtual courses. However, some strategies are sought when they are not performed in virtual environments in order to develop and promote them in other contexts and spaces. Hence, online training occurs, essential and substantially, as a mixture between the virtual and face attendance. In that way, the training paths and learning paths on the observed courses consist of the coexistence of parallel processes and feedback that occur in compensation movements of points in where relations, being the base of the elements, are greatly circumstantial and nonstructural, as those formations require that are supported by the intensive use of DTCI and VLE.